2016
DOI: 10.1080/14623943.2016.1214120
|View full text |Cite
|
Sign up to set email alerts
|

The third-space professional: a reflective case study on maintaining relationships within a complex higher education institution

Abstract: Stoltenkamp, J. (2017). The third-space professional: a reflective case study on maintaining relationships within a complex higher education institution. Reflective Practice, 18(1): 14-22. http://dx. AbstractThis paper showcases the work of Third Space professionals in a complex higher education (HE) setting, and specifically its impact on the building of trust relationships and innovative approaches. It makes use of a case-study methodological approach, reflecting on the experiences of various stakeholders wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…One is project management, which involves overseeing design and development and keeping track of projects . Regarding project managers, Hixon (2008) found that some instructional designers perceived themselves to be at the center of the course‐development project because they were responsible for managing the flow of the project, coordinating work with other professionals (Carré, 2015; Hixon, 2008; Pan & Thompson, 2009; Xu & Morris, 2007), and allocating and assigning resources (Stoltenkamp & Siebrits, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…One is project management, which involves overseeing design and development and keeping track of projects . Regarding project managers, Hixon (2008) found that some instructional designers perceived themselves to be at the center of the course‐development project because they were responsible for managing the flow of the project, coordinating work with other professionals (Carré, 2015; Hixon, 2008; Pan & Thompson, 2009; Xu & Morris, 2007), and allocating and assigning resources (Stoltenkamp & Siebrits, 2017).…”
Section: Resultsmentioning
confidence: 99%